Advisory Explosion or Audit Implosion? Excursus of Italian Regulatory and Non-Regulatory Positions in Private and Public Finance (European journal of volunteering and community-based projects, 2023)
In this paper we take into consideration two cases of advisory explosion in Italy between private and public finance respectively in regulatory and non-regulatory positions (abuse of dominant position).Given the need that Fiat Group Automobiles has to grow rapidly, and especially in foreign markets, Sergio Marchionne's policy in terms of internationalization is combined with that of establishing collaboration agreements that reduce the mass of investments to be financed and bring together competent on new markets.The negotiation between ASM and AEM for the corporate merger and the birth of A2A began in July 2006. After years of intense collaboration, the two Boards of Directors of the companies approved the Business Plan relating to the merger project; subsequently, the Boards of ASM and AEM approve the framework agreement on the structure and the main terms of the operation and at the same time the agreement relating to the guidelines concerning the merger signed between the Municipality of Brescia and the Municipality of Milan.